Making Mind Real: Adapting Tanya Luhrmann’s Theory to Non-Theistic Practices of Buddhism - Shabalina, Anastasiia (Journal for the Cognitive Science of Religion, 2024)
Tanya Luhrmann’s notable contribution to the cognitive study of religion consists of demonstrating that religious experience is based on purposeful practice of the believer. Through this practice, the objects of religious doctrine – gods and spirits – eventually begin to be perceived as more real and present. However, considering realness only in the context of encounters with invisible beings limits the theory to theistic religious traditions. This paper suggests that the process of transforming doctrine into real experience is also evident in Buddhist meditation practice, where encounters with gods and spirits are not the primary goal. Therefore, Luhrmann’s theory of real-making can potentially be extended by examining patterns common to both theistic and non-theistic religions in the transformation of religious ideas into concrete embodied experiences.